Characteristics of drought variation in winter using drought Indices during the period 1971-2010 : A case study of Khyber Pakhtunkhwa (Pakistan) (MAUSAM, 2016)
Generally drought is the outcome of reduction in precipitation for a long period of time. It can happen anywhere in the world and cause harmful effect to human life and eco system. There are different drought indices, derived for analysis and quantification of drought. In this study monthly precipitation and temperature data was used to analyze drought situation using Standardized Precipitation Evapotranspiration Index (SPEI), Standardized Precipitations Index (SPI) and Z-index (also known as China Z-index) for the period 1971-2010 over Khyber Pakhtunkhwa (KPK) province of Pakistan for winter season (December, January & February). Analyses were performed on 3, 6 and 12 month timescale for SPEI and SPI. Z-index is used to calculate drought/wet (flood) situation in winter season. Based on all these indices, dryness and wetness intensity varies with timescale and location. On basis of three time scale, during the years 1971, 1988, 2001 and 2002, majority of the stations of study area were under the drought conditions (of different intensities). SPEI and SPI sometime portray contrasting results, because the later does not take into account the effect of temperature. Based on SPEI, drought frequency increases from north to south. Dera Ismail Khan (D.I. Khan) & Kohat suffered drought conditions for highest number of year, while Balakot the least. Contrary to this D. I. Khan has the least number of drought years based on SPI.